REINSERTING AFRICAN AGENCY INTO SINO-AFRICA RELATIONS (The Strategic Review for Southern Africa, 2020)
The Second Forum on China-Africa Cooperation Summit held in December 2015 marked the significance and extent to which China's relationship with Africa is changing. China's tripling of its financing commitment to US$60 billion signalled its confidence in the economic transformation prospects of the African continent. The changing Sino-Africa relationship is underpinned by a shift towards a more balanced partnership that recognises Africa's socio-economic and political priorities, beyond the demand for its natural resources. This paper seeks to help unpack the different dimensions of the links between Africa and China including the "untold story" of the relationship. A story about the significant number of Africans who live in or frequently visit China, and the increasing flow of African investments  and tourists into China. Sino-Africa relations have evolved to the extent that African countries are taking a more assertive role when it comes to investment and signing trade deals, ensuring that their interests are protected.
Keywords: Second Forum; China-Africa; Cooperation Summit; relationship; economic; transformation; African continent; Sino-Africa; Africa's socio-economic; natural resources; South Africa; policy; political; projects; financial assistance; modernisation; medical; agricultural; HIV/AIDS; Support; development